(untitled) (Management Dynamics, 2020)
This study aims to explore the views of general investors on their IPO investments in the primary market. Using a judgemental sampling, the views of 109 general investors who actively participated in the primary market has been employed in the study from Pokhara City. The study revealed that banking and finance followed by hydropower are the most preferred sectors of buying common stocks in the primary market with the expectation of long term returns. There is a significant different perception on both risk and return from IPO investment between male and female investors. The study also found that government’s policy announcements followed by the size of the firm that issues IPOs are the major determinants of IPO return and risk among investors. Increasing paid up capital for business expansion is the important reason for issuing IPOs by the companies while creating exit route for existing shareholders is the least.